Effects of noise exposure on auditory brainstem response and speech-in-noise tasks: a review of the literature. (25th January 2019) - Le Prell, Colleen G.
Abstract: Objective: Short-term noise exposure that induces transient changes in thresholds has induced permanent cochlear synaptopathy in multiple species. Here, the literature was reviewed to gain translational insight into the relationships between noise exposure, ABR metrics, speech-in-noise performance and TTS in humans. Design: PubMed-based literature search, retrieval and review of full-text articles. Study Sample: Peer-reviewed literature identified using PubMed search. Results: Permanent occupational noise-induced hearing loss (NIHL) is frequently accompanied by abnormal ABR amplitude and latency. In the absence of NIHL, there are mixed results for relationships between noise exposure and ABR metrics. Interpretation of speech-in-noise deficits is difficult as both cochlear synaptopathy and outer hair cell (OHC) loss can drive deficits. Reductions in Wave I amplitude during TTS may reflect temporary OHC pathology rather than cochlear synaptopathy. Use of diverse protocols across studies reduces the ability to compare outcomes across studies. Conclusions: Longitudinal ABR and speech-in-noise data collected using consistent protocols are needed. Although speech-in-noise testing may not reflect cochlear synaptopathy, speech-in-noise testing should be completed as part of a comprehensive test battery to provide the objective measurement of patient difficulty.